Standard test method for evaluating the microstructure of graphite in iron castings. (ASTM International, 2006)
This test method covers the classification of graphite in cast irons in terms of type, distribution, and size. This test method is intended to be applicable for all iron-carbon alloys containing graphite particles, and may be applied to gray irons, malleable irons, and the ductile (nodular) irons.